Problems and perspectives of sustainable trade development in China under the one belt one road initiative - Zhi Ji; George Abuselidze; Valeriia Lymar (E3S Web of Conferences, 2021)
In the paper the authors proved that China's growth towards dominance in international trade has begun recently, but, on average, the growth of China's trade volume has doubled every four years over the past three decades. The paper analyses that the rapid growth of the Chinese economy provides all countries around the world especially neigh boring countries, with a chance of interconnected development, which had a decisive impact on the economic prosperity of the world economy at the end of the last and at the beginning of this century. The key priority of Chinese economic policy was called attracting FDI, but gradually it focused on foreign direct investment (FDI) from China. Therefore, the "one belt, one road" initiative has brought maximum effect not only on the country itself, but on the entire global economy, and has become the basis for multilateral economic development. Accordingly, we have come to the conclusion that the project the "one belt, one road" has a goal to strengthen the geopolitical cooperation between Asia and Europe, so it is Ukraine that is important in its implementation. Ukraine is a strategically important logistics hub between Asia and Europe. It is proved that Ukraine is now a promising country in Eastern Europe and has a significant deferred purchasing power potential, which will increase if the political and economic situation in the country stabilizes.
Keywords: F02; F13; F63; O24; 330; Trade Policy; Trade Development Strategy; One Belt; One Road; Export-Import Operations